Aplikasi Pengenalan Huruf Untuk Anak-Anak Berbasis Mutimedia Pada TK Alfalaq - Harun Musa (Journal of Education and Teaching Learning, 2023)
Letter recognition learning media that is taught for early childhood educaton so far generally still uses books or fictures that make it possible to develop an innovation which is a book or two dimensional pictures Kindergarten is a place for coaching aimed at children from the age of four to the age of six which is carried out through the provision of educational stimuli to assist physical and spiritual growth and development so that children are ready to enter further education. teachers can work with various parties to provide this learning media. Teachers themselves can study various software to create learning media that are tailored to the needs of their students. One software that can create various media such as videos, animations, images, sounds, and so on in an easy way is Adobe Flash. The content required by users can be accessed easily and is equipped with multimedia facilities that are able to combine text, images and sound in one device. The method used in this research is descriptive method, namely research that seeks to solve existing problems systematically based on existing data.